LIMITATION OF FREEDOM BY THE STATE FOR PANDEMIC CONTROL COVID-19 (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2012)
The present study aims to assess the power of state and municipal managers in the emergency confrontation of the COVID-19 pandemic by extraordinary measures of social isolation and quarantine that imply the restriction of fundamental rights of the citizen such as freedom of movement, right of assembly, exercise of activity among others. Through the bibliographic procedure, with a qualitative approach, using, in terms of writing, the deductive method, we seek an answer about the possibility or not for the edition, at regional and local level, of restrictive measures, fundamental rights without legal support. A response that does not dispense with the guidelines of the legal system, which has the Constitution as the highest point in organizing State powers, subjecting them to limits specific to constitutional discipline in defense of public freedoms. Furthermore, due to the lack of other studies on the point, the research around it is justified, maximally in view of the various questions already existing on the subject within the scope of the Judiciary. The study concludes that there is a need for a legal provision for stipulating measures that restrict fundamental rights, under penalty of violation of the Democratic Rule of Law.